MACRO ECONOMIC POLICIES IN INDONESIA - Hendri Hermawan Adinugraha (Annals of the University of Craiova for Journalism, Communication and Management)
Indonesia as a country with the largest Muslim population in the world, Indonesia has not yet been ranked the highest in various fields of Islamic economics. Therefore, this study intends to analyze fiscal and monetary policies that can be the basis for developing sharia economic policies in Indonesia. This research method uses a qualitative type with a library research approach. The results of the study found that fiscal policy in an Islamic economic review is an obligation of the state to become the rights of the people, so that fiscal policy is not only a necessity for economic improvement and increasing people’s welfare, but rather on the creation of a fair economic distribution mechanism. Monetary policy in the view of Islamic economics should be free from elements of usury and bank interest. Because in the perspective of Islamic economics, usury which includes bank interest is strictly prohibited. With this prohibition, bank interest, which in a capitalist economy becomes the main instrument of monetary management, is no longer valid. The Indonesian nation as a country with a majority Muslim population is ideally able to implement fiscal and monetary policies that are in accordance with Islamic economic principles or Sharia compliance.